2004
DOI: 10.1016/s1054-139x(03)00528-7
|View full text |Cite
|
Sign up to set email alerts
|

Heightened vulnerability and increased risk-taking among adolescent chat room users: results from a statewide school survey

Abstract: Because chat room use serves as an indicator of heightened vulnerability and risk-taking, parents and others need to be aware of potential dangers posed by online contact between strangers and youth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
9
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…The research results suggest that parents should pay special attention to children who are more heavily involved in social networking activities. This parallels earlier research findings that children who had greater levels of online chatting were more likely to exhibit risky behavior (Beebe et al, 2004).…”
Section: Discussionsupporting
confidence: 88%
“…The research results suggest that parents should pay special attention to children who are more heavily involved in social networking activities. This parallels earlier research findings that children who had greater levels of online chatting were more likely to exhibit risky behavior (Beebe et al, 2004).…”
Section: Discussionsupporting
confidence: 88%
“…Instead, vulnerabilities such as family conflict, depression, conversing with unknown people about sex, and sending personal information to strangers have been identified 37. Evidence also suggests that adolescents who have been victims of childhood abuse (including physical or sexual abuse and/or neglect) may be at particular risk, because they are more likely to visit chat rooms,8 be solicited sexually online and offline,9 and receive aggressive sexual solicitations3 than their nonabused peers. Moreover, childhood abuse victims are likely to experience subsequent physical and sexual revictimizations and exploitations,1013 making it plausible that vulnerabilities for these types of revictimizations carry over to Internet-initiated victimization.…”
mentioning
confidence: 99%
“…A disproportionate number of adolescents, who were frequent ‘chat-room-users’ have run away from home and experimented with drugs and alcohol 13. On the other hand, many adolescents have searched for accurate information about sex online 14 15.…”
mentioning
confidence: 99%
“…Youth Risk Behavior Surveillance Reports indicated that 47.8% of high school students have had sex 16. One study reported the average frequency of coital events was 0.94 per week17; young internet users seeking sex partners may be at high risk of STI 13 18. However, because the internet has the ability to provide accurate educational information, using it also to provide STI services has much appeal.…”
mentioning
confidence: 99%